Value for Money Audit and Financial Performance of Local Governments in Eastern Uganda: A Case of Butaleja District in Eastern Uganda - Basirika Bayati (Uganda Christian University, 2024)
The study looked at the effect of Value for Money audit on the financial performance of Butaleja District. Specifically, it aimed to determine the impact of verification of accounting data, records examination, and internal controls on financial performance. A cross-sectional survey was employed, involving a population of 40, with a sample size of 36 respondents determined using the Slovene’s formula. The study utilized simple random sampling and purposive sampling techniques. The research findings revealed that verification of accounting data, records examination, and internal controls significantly influence financial performance in Butaleja District. It also indicated that thorough verification processes, strategic records examination, and robust internal controls contribute positively to financial performance. The study recommends the implementation of effective verification mechanisms, comprehensive records examination protocols, and strengthened internal control systems to enhance financial performance in Butaleja District. Lastly, the study concludes that Value for Money audit plays a crucial role in optimizing financial performance and ensuring fiscal accountability within the local government context.